Influence of Iron Nano Co-polymer Catalysts on the Liquid Hydrocarbons Production in the Synthesis Fischer Tropsch - Abdulqadier Hussien Al-Khazraji (Journal of Global Pharma Technology, 2016)
In this paper the synthesized composites were used in the Fischer - Tropsch reaction(FT) which compared the catalytic activity of catalysts based on Co-polymer (COP)such Styrene Butadiene Rubber (SBR)) and Polyethylene terephthalate (PET)) with catalysts. The COPS were supported within polypropylene (PP) in the system nano Fe-Paraffin-polymer. The behavior of Co-polymers gave significant effects in the creation of nano catalysts by stabilizing the nanoparticles, and producing new active sites for synthesized hydrocarbons from CO and H2as sources of energy. Catalytic materials shows sensitivity and selectivity in the Fischer-Tropsch process with three phase slurry reactors. The greatest conversion of CO was obtained in 66%, which forming hydrocarbons liquid reach to 60g/m3for catalysts copolymer(SBR) , whilst using catalyst with PP reduce the conversion of CO to 50% which also forming 38g/m3ofhydrocarbons. The iron nano particles were characterized by AFM technique and XRD in the polymer-paraffin matrix.Keywords: Fischer-Tropsch (FT), Three phase slurry reactor, Polymers.